Arguing about Indigenous administrative participation in the Whitlam era: A representation theory analysis. Issue 1 (7th December 2018) - Ganter, Elizabeth
Abstract: In 1974 Prime Minister Gough Whitlam established the Royal Commission on Australian Government Administration ('the Commission'), appointing HC Coombs as chair. The Commission's brief was 'to inquire into and report on the administrative organization and services of the Australian Government' giving particular attention to, among other issues, public servants' 'participation in forming policy and making decisions'. From the outset the Commission aligned itself with the view that Aboriginal people were 'less than proportionately represented in the administration'. The Commission asked CD Rowley to prepare a report on Aboriginal issues. Barrie Dexter, Secretary of the newly established Department of Aboriginal Affairs and Charles Perkins, Assistant Secretary and Arrernte man from Central Australia, both gave evidence to the Commission. The competing ideas on Indigenous administrative participation expressed by Coombs, Rowley, Dexter and Perkins in the course of the Commission will be considered through the lens of representation theory. While all four doubted the capacity of the bureaucracy to provide a meaningful channel for Indigenous representation internally, each argued from a different view of representation. Understanding their positions on how Indigenous people should be represented in public administration, including their assumption that there would also be external Indigenous representation, could shed light on tensions that are still present today. Abstract : The Royal Commission on Australian Government Administration established by the Whitlam Government in 1974 deliberated on how to achieve Indigenous participation in the administration of government. This article draws on representation theory to show the continuing relevance of its insight that government should support Indigenous representation both internally and externally.